Affordable Rental Housing : Making It Part of Europe's Recovery - ElFayoumi, Khalid; Karpowicz, Izabela; Lee, Jenny; Marinkov, Marina (Washington, D.C. : International Monetary Fund, 2021)
Many European economies have faced pressure from rental housing affordability that has widened social and economic divergence. While significant country and regional differences exist, this departmental paper finds that in many advanced European economies a large and rising share of low-income renters, the young, and those living in cities is overburdened. In several locations, middle-income groups also increasingly face rental affordability issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Political Economy